STRATEGI PEMASARAN DALAM UPAYA MENINGKATKAN PENJUALAN PRODUK (Studi Kasus Pada Toko Batik Benang Raja Surabaya) - Rahman, Muhammad Alif; Arusita, Dora Rabayana (Jurnal Baruna Horizon, 2024)
Abstract. The purpose of this observation is to determine the marketing strategy of the Surabaya branch of the Raja Yarn Batik shop by using a marketing mix. This study uses a qualitative descriptive approach with data collection including observation, interviews, documentation and triangulation. The informants in this study consisted of 3 key informants and 2 supporting informants.The results of this study indicate that the role of the product in supporting increased sales at the Batik Shop Yarn Raja is to maintain the quality of products and ingredients used in accordance with consumer desires. The role of prices in supporting the increase in sales at the Batik Shop Raja Raja Surabaya by setting prices in accordance with the quality of its products and target markets. The role of the place in increasing sales at Surabaya Batik Shop is the selection of strategic locations and in the center of the crowd. Promotion's role in increasing sales at the Surabaya Raja Raja Batik Shop utilizes social media as a form of promotion such as Instagram. So the four components such as products, prices, places and promotions in the marketing mix can increase sales of batik products.